Education for Stroke Caregivers to Reduce Burden - Khomarun Khomarun; Wawan Ridwan Mutaqin; Noerdjanah Noerdjanah (Lembaga Publikasi Ilmiah Nusantara, 2026)
Stroke is one of the leading causes of disability, resulting in patients’ dependence on informal caregivers and potentially causing physical, psychological, and social burdens. This study aimed to determine the effect of educational interventions on caregiver burden in Ngemplak District, Boyolali, and Colomadu District, Karanganyar. This quantitative study used a pretest-posttest design and a paired-samples t-test. The Shapiro-Wilk normality test indicated that the data were normally distributed. The sample consisted of 16 caregivers who met the inclusion criteria. The results showed that the mean caregiver burden score increased from 28.00 ± 1.862 at pre-test to 33.13 ± 2.825 at post-test, with a statistically significant difference (t = -5.045; p = 0.000). Qualitative interview findings revealed that several caregivers experienced a reduction in heavy burden levels after the intervention, accompanied by decreased physical fatigue, improved ease in caregiving activities, and greater patient independence. However, economic difficulties and high patient dependency remained major challenges for some caregivers. Overall, the educational intervention demonstrated a significant influence on caregiver burden both quantitatively and qualitatively. Education is therefore recommended as an ongoing community-based intervention to support caregivers of stroke patients.